STUDENTS’ PERCEPTION AND MOTIVATION TOWARDS DIGITAL TEXT IN LEARNING READING - Mela Sari Satin; Rahma Ilyas; Agus Rofi'i (Journal of English Language Learning, 2018)
Reading plays an important role in process of language. Selfefficacy belief about reading, access to interesting to read English text and interaction with media tool is factors that motivate students to read. The aims of the research are: 1) to reveal the students’ perception to use of digital text in learning reading; and 2) to reveal students’ motivation to use of digital text in learning reading. Reseacher used case study as the research design. The participants in this research is the students of X TITL (Teknik Instalasi Tenaga Listrik) D grade one of vocational high school in Majalengka. Data collection techniques were observation, questionnaire and interview. The findings of the research showed that students have 75% as good motivation, and they agreed advantages of digital text as a digital learning reading but there are faced the problem in reading like the vocabulary, the condition of class and ability to do exercise make them difficult. The conclusion of this research are students claim that using digital text can help them in learning reading and given the positive responses about digital text. Digital text is different from print paper where some of advantages they feel such as digital text give them different way in learning, pictures in digital learning make them more understood and interested, then digital text more weight less and lighter. Furthermore, digital text can increase students’ motivation.Keyword: Reading, Digital Text, Perception, Motivation